Global support at the click of a button: How digital remittances help Ukraine during crises - Yevheniia Polishchuk; Yana Valko; Olena Shuplat; Yurii Vasylyshen (Geopolitics under Globalization)
In recent years, Ukraine has faced two major crises: the COVID-19 pandemic and Russia’s military invasion of Ukraine. Digitalization allowed the extension of financial inclusiveness for the recipients and building financial resilience through remittances. They became one of the most important sources of survival for vulnerable populations. The aim of the paper is to examine how remittances can help Ukraine during the crises. The main research methods are descriptive statistical analyses to examine remittance trends and patterns. The data were taken from the open sources of the National Bank of Ukraine, Statista, the European Commission, Migration Data Portal, World Bank, and CoinLaw. The results showed that the share of informal remittance channels, although present, tends to decrease compared with the official ones. Poland is the main supplier of money in Ukraine. The average transaction value has also decreased from USD 3,540 thousand in 2017 to USD 1,750 thousand by 2024, which is due to the increase in the number of platforms that allow small transfers. It also pushed the increasing numbers of users of digital remittance platforms from 1,500 thousand in 2019 to 2,700 thousand in 2024. It confirmed that remittances for Ukrainians during crises are one of the sources for survival and potentially for recovery. The study can be useful during the development of different programs of livelihood support and recovery of Ukraine by engaging the Ukrainian diaspora.